Hyperactive CREB signaling pathway involved in the pathogenesis of polycystic ovarian syndrome revealed by patient-specific induced pluripotent stem cell modeling - Huang, Chu-Chun; Chen, Mei-Jou; Lan, Chen-Wei; Wu, Chia-Eng; Huang, Mei-Chi; Kuo, Hung-Chih; Ho, Hong-Nerng (Fertility and sterility, 2019)
To study whether and how the pathogenesis of polycystic ovarian syndrome (PCOS) is related to epigenetic aberrations. A case-control experimental study. Tertiary university hospital. Eighteen patients with PCOS and ten non-PCOS control subjects. Patient-specific induced pluripotent stem cells (iPSCs) were obtained from skin fibroblasts through the application of nonviral episomal reprogramming and were differentiated into ovarian granulosa cells (GCs) with the use of a cocktail of growth factors. Primary ovarian GCs were collected during transvaginal oocyte retrieval surgery. Characterization and functional validation of iPSC-derived GCs were conducted. Whole-genomic DNA methylation profiles in women with and without PCOS in both iPSC-derived GCs and primary adult GCs were analyzed with the use of the Illumina 850K MethylationEPIC Beadchip. The iPSC-derived GCs successfully expressed GC-associated genes and aromatase activity after differentiation. Whole-genomic DNA methylation analysis of the iPSC-derived GCs and adult GCs both revealed a hyperactive CREB signaling pathway in the PCOS group compared with the control group. The expression of CREB-binding protein (CBP) mRNA was significantly higher in the iPSC-derived GCs in the PCOS group, and the expression of CBP protein was also significantly higher in the primary GCs from women with PCOS. The combination of DNA methylomic analysis in primary adult GCs and iPSC-derived GCs showed that a preserved persistent hyperactivation of the CREB signaling pathway might be involved in the pathogenesis of PCOS. These results could have implications on the early developmental origin, inheritance nature, and environmental interaction effects of this disease. Vía de señalización CREB hiperactivada involucrada en la patogénesis del síndrome de ovario poliquístico revelado por el modelado de células madre pluripotentes inducidas en una paciente específica Estudiar si y cómo la patogénesis del síndrome de ovario poliquístico (PCOS) está relacionada con aberraciones epigenéticas. Estudio experimental de caso-control. Hospital universitario terciario. Dieciocho pacientes con PCOS y diez sin PCOS cómo sujetos de control. Células madres pluripotentes inducidas de paciente especifica (iPSCs) fueron obtenidas de fibroblastos de la piel a través de la reprogramación episomal no viral y fueron diferenciadas a células de la granulosa ovárica (GCs) con el uso de un cóctel de factores de crecimiento. Las GCs ováricas primarias fueron obtenidas durante la cirugía transvaginal de recuperación de ovocitos. Se llevó a cabo la caracterización y validación funcional de las GCs derivadas de iPSCs. Los perfiles de metilación del ADN genómico completo en mujeres con y sin PCOS, en las GCs derivadas de iPSCs y GCs adultas primarias fueron analizados con el uso del Illumina 850K MethylationEPIC Beadchip. Las GCs derivadas de iPSCs expresaron genes asociados a GC y actividad de la aromatasa después de la diferenciación. En el análisis de la metilación del ADN genómico completo de las GCs derivadas de iPSCs y GCs adultas reveló una hiperactivada vía de señalización CREB en el grupo de las PCOS comparado con el grupo control. La expresión de mRNA de la proteína de unión CREB (CBP) fue significativamente mayor en las GCs derivadas de iPSCs en el grupo PCOS, y la expresión de la proteína CBP también fue significativamente mayor en las GCs primaria de mujeres con PCOS. La combinación del análisis del ADN metilómico en GCs adultas primarias y las GCs derivadas de iPSCs demostró que una hiperactivación persistente y conservada de la vía de señalización CREB puede estar involucrada en la patogénesis de las PCOS. Estos resultados podrían tener implicaciones en el origen temprano del desarrollo, naturaleza de la herencia y los efectos de interacción ambiental de esta enfermedad.